2023
DOI: 10.3390/molecules28135257
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Oil Displacement Effect of Amphiphilic Polymer Heavy Oil Activator

Abstract: A heavy oil activator is an amphiphilic polymer solution that contains hydrophilic and oleophobic groups. It can enhance heavy oil recovery efficiency. This paper studied the changes in the distribution of the remaining oil after activator flooding and the performance of heavy oil’s active agent. Nuclear magnetic resonance spectroscopy, laser confocal microscopy, microscopic visualization, and CT scanning techniques were used to analyze crude oil utilization, and the distribution characteristics of the remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…After mechanical shearing, the viscosity retention rate of HPDACs in ultrapure water and simulated brine was higher than that of PAM and the dendritic polymer, indicating the excellent shear resistance and good viscoelasticity of HPDACs. In addition, in order to effectively avoid chromatographic separation problems of BPSMs, both hydrophobic and hydrophilic groups were introduced into BPSMs [31] to improve the ability to expand the swept volume and oil displacing efficiency [32,33]. Zhu et al [34] synthesized an amphiphilic polymer with twintailed hydrophobic groups (TAP).…”
Section: Introductionmentioning
confidence: 99%
“…After mechanical shearing, the viscosity retention rate of HPDACs in ultrapure water and simulated brine was higher than that of PAM and the dendritic polymer, indicating the excellent shear resistance and good viscoelasticity of HPDACs. In addition, in order to effectively avoid chromatographic separation problems of BPSMs, both hydrophobic and hydrophilic groups were introduced into BPSMs [31] to improve the ability to expand the swept volume and oil displacing efficiency [32,33]. Zhu et al [34] synthesized an amphiphilic polymer with twintailed hydrophobic groups (TAP).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, amphiphilic polymers with double-tail hydrophobic groups displayed improved temperature resistance, salt resistance, and mechanical shear resistance at equivalent polymer solution concentrations. Zhi [23] employed amphiphilic polymer as a heavy oil activator and investigated the changes in residual oil distribution following activator displacement, along with its performance in heavy oil activation. The results demonstrated that the activator could reduce oil-water interfacial tension, break down and disperse recombination fractions in heavy oil, and decrease heavy oil viscosity.…”
Section: Introductionmentioning
confidence: 99%